Data and scripts for "Optical line shapes of color centers in solids from classical autocorrelation functions" - Linderälv, Christopher; Österbacka, Nicklas; Wiktor, Julia; Erhart, Paul (Chalmers University of Technology, 2024)
This record contains data and code that accompany the paper "Optical line shapes of color centers in solids from classical autocorrelation functions". Specifically it includea databases in ase sqlite format (*.db) with reference data from density functional theory calculations. These data were used in the construction of the machine-learned potential model using the neuroevolution potential (NEP) methodology. The model (nep.txt) is included in a format suitable for the GPUMD package (https://gpumd.org).

Note that the atom type information in the databases already includes the labeling of the defect environment that is expected by the NEP model, according to the following rules

Si(gs) →  P

C(gs) → N

Si(ex) → S

C(ex) → O

The "bulk" species (Si, C) remain unchanged.
Keywords: Physical Sciences; Fysik